Sustainable development in mountain regions Southeastern Europe - Zhelezov, Georgi (Springer Netherlands, 2011)
The mountain regions in Southeastern Europe are unique natural regions of great beauty and ecological value, and home of the head waters of major rivers. They constitute a major ecological, economic, cultural, recreational and living environment in Europe, shared by numerous cultures and countries. The Southeastern European Mountain Regions are an important reservoir for biodiversity and habitats in Europe. A great number of protected areas; national parks, nature parks, reserves and nature monuments are located in these regions. From a socio-economic point of view the mountain regions are among the poorest areas in the Southeastern European countries, but they have potential for the implementation of successful economic activities. There are opportunities for development of these regions and, in particular, for trans-border integration and co-operation. This book brings together research results from experts from all Balkan countries working on the problems of the mountain regions in Southeastern Europe. The volume focuses on the challenges taking place along the rapid transformation in land use, biodiversity, tourism, nature risk and bio-productivity due to the global changes and particularly due to the local impacts of climate change. The key questions for discussion are: Biodiversity, nature protection and conservation; Natural disasters and risk management; Social-economical development of the mountain regions; Spatial planning in the development of the mountain regions; Sustainable practices and politics for land use; Transborder co-operation.